2012
DOI: 10.1134/s160767291203009x
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acids bounded to the mitochondrial membranes as a substrate for ATP synthase

Abstract: 158Starting from 1961, two models for transforma tion of the energy of oxidation reactions in mito chondria have been discussed in the literature. The model of Mitchell [1] implies that the multienzyme phosphorylation system can work in a dissociated form, while the other model (by Williams) considers a supercomplex [2].We have earlier demonstrated that the phosphory lation system is able to function in both modes, corre sponding to two structural states of mitochondria [3]. The operation modes of the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…Numerous studies of the past two decades [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] indicate that the local model is more likely to be realized in real cells. The experiments, while often not unambiguous [23][24][25][26], did reveal however a puzzling property of protons migrating along the membrane surface -they appear to remain on the surface for too long, making surface transport surprisingly long-distant, up to tens of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies of the past two decades [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] indicate that the local model is more likely to be realized in real cells. The experiments, while often not unambiguous [23][24][25][26], did reveal however a puzzling property of protons migrating along the membrane surface -they appear to remain on the surface for too long, making surface transport surprisingly long-distant, up to tens of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…The same effect was observed on phosphorylating mitochondria (in the presence of substrates: succinate, ADP, phosphate) under conditions of close docking of the inner and outer mitochondrial membranes in medium with decreased tonicity (120 mOsm) [15].…”
Section: Fraction Of "Energized" Protons On the Surface Of Membranes mentioning
confidence: 50%
“…In our works, we showed experimentally the appear ance of membrane bound Bronsted acids carrying free energy excess on membranes of mitoplasts [13] and mito chondria [14,15]. Based on these experiments, we wrote a full equation of the thermodynamic potential of hydro gen ions (ΔG) as the sum of the electrochemical Mitchell's potential (ΔμH) and the solvation potential (Δμ solv ) resulting due to partial dehydration of membrane bound protons:…”
Section: Fraction Of "Energized" Protons On the Surface Of Membranes mentioning
confidence: 99%
“…Proton binding at the interface was firstly reported in the biological system during the functioning of rhodopsin proton pumps (34). It was also shown that the operation of proton pumps in intact mitochondria and mitochondria without outer membranes leads to the formation of the membrane-bound protons fraction (35,36). Therefore, the protons with an excess of free energy may be retained on the membrane-water interface and used for ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%